Music and Mathematics: Processing Repetition Techniques with the Least Common Multiple (LCM) in Rajékan Music Composition - Budiawan, Hery; Ananda, Rizky Fauzy (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
This article aims to find a new way to process repetition in musical composition with the least common multiple (LCM) mathematical approach. Music and mathematics have a very close relationship; in music, the element of mathematics with the derivation of physical science is the most relevant and always interesting study of musical composition. This study aims to analyse the music composition of Rizky Fauzy Ananda’s work, Rajékan, by looking at mathematical theory with the approach of The least common multiple (LCM). The method used with practice-led Research as an approach to music composition. The creation research methodology used is Artistic Research through a Practice-Led Research approach which is also integrated with mathematical theory and musicology, especially music composition. The results of this creative Research prove that repetition in music and in the context of life is important and mathematics always present in human life. Repetition has largely underpinned development in music. In the context of life, reps are things that always exist in everyday life, such as worship activities and lifestyles. Such repetitive phenomena can also provide certain learning or meaning for the individual. In the context of education, reps are the easiest and most basic way of learning to learn and recall about understanding something. Repetition processing whose ideas come from the phenomenon of researchers’ self-experience, produces two repetition processing techniques with the LCM mathematical style (1) magnification and reduction of sound values that make up the cycle, (2) imitation.